ANALYSIS OF STUDENT’S MATHEMATICAL REASONING ABILITY IN SOLVING MATHEMATICAL PROBLEM BASED ON HOTS - Susi Herawati; Puspa Amelia (FKIP Universitas Muhammadiyah Tangerang, 2021)
This study was focused onanalyzing student’s mathematical reasoning abilities in solving Higher Order Thinking Skill (HOTS) problems anddetermining the level of student understanding of HOTS questions. The researchmethod is qualitative descriptive with 12 subjects. Based on the results of the test, the subject’s reasoning abilities were grouped into 3 categories of reasoning abilities, namely high, moderate and low. The results showed that students who had high reasoning abilities were able to fulfill the 7 mathematical reasoning indicators very well at each stage of real analysis problem solving and were able to work on HOTS levelquestions to analyze and create. Students with moderate reasoning abilities were only able to fulfill several indicators of mathematical reasoning, namely presenting written statements, solving problems as planned and checking again. Students who had low reasoning abilities were not able to understand the questions well, so students cannot solve it. Based on the results of the questionnaire, it was concluded that 46.67% of students could understand the HOTS problem well, 33% of the students could not plan the solution, namely writingdown the information that was known in answering the questions, and 33% of the students were not able to check the validity of an argument and draw conclusions on the evidence. Furthermore, it was obtained the relationship between student’s mathematical reasoning abilities and the level of student understanding of HOTS-oriented questions which fulfilled the linear regression equation Y = 71.574 + 0.009X.This model showed that the level of student understanding of HOTS-oriented questions had a positive effect on learning outcomes. Based on the research results, it was suggested that lecturers provide more training related toproof with the aim of improving students' mathematical reasoning abilities.